Towards Protecting Critical Infrastructures - Caldeira, Filipe (2015)
Critical Infrastructures (CIs) such as power distribution are referred to as “Critical” as, in case of failure, the impact on society and economy can be enormous. CIs are exposed to a growing number of threats. ICT security plays a major role in CI protection and risk prevention for single and interconnected CIs were cascading effects might occur. This chapter addresses CI Protection discussing MICIE Project main results, along with the mechanisms that manage the degree of confidence assigned to risk alerts allowing improving the resilience of CIs when faced with inaccurate/inconsistent alerts. The CockpitCI project is also presented, aiming to improve the resilience and dependability of CIs through automatic detection of cyber-threats and the sharing of real-time information about attacks among CIs. CockpitCI addresses one MICIE's shortcoming by adding SCADA-oriented security detection capabilities, providing input for risk prediction models and assessment of the operational status of the Industrial Control Systems.